PENERAPAN MODEL PEMBELAJARAN TIPE NUMBER HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI SISTEM DARAH PADA MANUSIA DI SMP NEGERI SATU ATAP DESA TUTUWAWANG - Erbabley, Adriana; Tuaputty, Hasan; Arini, Ine (Program Studi Pendidikan Biologi FKIP Unpatti, 2021)
Background: This study aims to determine the improvement of student learning outcomes in class VIII of SMP Negeri One Roof Tutuwawang on the material of the Human Circulatory System by applying Number Head Together learning. Methods: This study uses descriptive analysis which is used to determine students' cognitive, affective, and psychomotor learning outcomes. Results: The results showed that the mastery of students' biology concepts before the implementation of Number Head Together learning was very low. This can be seen from the average score obtained by students on the initial test, which is 10.46 from the KKM KD that is set, which is 70 which is included in the failed qualification. After the implementation of Number Head Together learning, the results of the formative test obtained by the students became better with an average percentage of achievement on the formative test, which was 79.49%. Conclusion: The application of the Numbered Head Together (NHT) Learning Model can improve learning outcomes on the material Circulatory system in humans in Class VIII SMP Negeri One Roof Tutuwawang by showing the results of the final test of 18 students and learning outcomes increase, classically successful, although with lower qualifications. different and are in the good category. Individual learning mastery is able to be physically achieved